2020
DOI: 10.33308/26674874.2020342204
|View full text |Cite
|
Sign up to set email alerts
|

Üstün Yetenekli Öğrencilerin Matematik Kaygısı ve Mükemmeliyetçilik Düzeylerinin İncelenmesi

Abstract: Bu araştırma, üstün yetenekli ilkokul 3. ve 4. sınıf öğrencilerinin mükemmeliyetçilik düzeylerinin, matematik kaygısını yordama gücünü incelemek amacıyla yapılmıştır. Araştırmanın çalışma grubunu İstanbul’da üstün yeteneklilere yönelik eğitim veren iki özel eğitim kurumunun 3. ve 4. sınıfında 2017-2018 bahar yarıyılında öğrenim gören 121 öğrenci oluşturmaktadır. Verilerin toplanmasında, öğrencilerin matematiğe yönelik kaygı düzeylerini belirlemek amacıyla geliştirilen Matematik Kaygısı Ölçeği (Bindak, 2005) ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Using the scale developed by Bindak (2005), several studies have been carried out in different cities and districts, at different grade levels, in different years and with different research methods (Aydın & Keskin, 2017;Berber, 2021;Dede & Dursun, 2008;Küçük, 2019;Yurt & Kurnaz, 2015). However, while some studies found the Cronbach's alpha coefficient to be around .70 (Erdik, 2018;Şimşek et al, 2017;Tuncer & Yılmaz, 2016) some studies had values of .80 and above (Akgül & Nuhoğlu, 2020;Aydın & Keskin, 2017;Küçük, 2019;Şahin, 2018). For this reason, a number of different Cronbach's alpha coefficient has been reported in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Using the scale developed by Bindak (2005), several studies have been carried out in different cities and districts, at different grade levels, in different years and with different research methods (Aydın & Keskin, 2017;Berber, 2021;Dede & Dursun, 2008;Küçük, 2019;Yurt & Kurnaz, 2015). However, while some studies found the Cronbach's alpha coefficient to be around .70 (Erdik, 2018;Şimşek et al, 2017;Tuncer & Yılmaz, 2016) some studies had values of .80 and above (Akgül & Nuhoğlu, 2020;Aydın & Keskin, 2017;Küçük, 2019;Şahin, 2018). For this reason, a number of different Cronbach's alpha coefficient has been reported in these studies.…”
Section: Introductionmentioning
confidence: 99%